2017
DOI: 10.5455/jicm.22.253019
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Indices and Cardiovascular Risks Factors in HIV Infection in Southern Nigeria

Abstract: not by increased levels of LDL-C have been associated with HAART (1). Insulin resistance, impaired glucose tolerance, impaired fasting glucose and diabetes mellitus are glucose metabolism disorders also reported in persons with HIV infection with and without HAART (2). The exact etiologic mechanisms for development of these disorders are still uncertain because not all of the patients exposed to the same HAART regimens are similarly affected. Alterations in acute phase response proteins in response to acute or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
9
3
0
Order By: Relevance
“…Findings from this study revealed that total cholesterol; LDL-C and TG were significantly higher in the HIV- infected study group compared to the uninfected control group. This is in line with the study of Nsonwu et al [51], who also reported similar findings. Dyslipidaemia in HIV-infected individuals has been attributed to elevated apolipoprotein levels, increased hepatic synthesis of TG and VLDL-C, decreased clearance of TG, acute-phase proteins, and to the effects of viral infection itself.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings from this study revealed that total cholesterol; LDL-C and TG were significantly higher in the HIV- infected study group compared to the uninfected control group. This is in line with the study of Nsonwu et al [51], who also reported similar findings. Dyslipidaemia in HIV-infected individuals has been attributed to elevated apolipoprotein levels, increased hepatic synthesis of TG and VLDL-C, decreased clearance of TG, acute-phase proteins, and to the effects of viral infection itself.…”
Section: Discussionsupporting
confidence: 93%
“…Among HIV-infected participants in this study, the levels of HDL-C were significantly lower compared to un-infected control group. These findings are consistent with the report of Nsonwu et al [51], who reported that lower levels of HDL among HIV-infected individuals on ART compared to uninfected controls. Lower HDL-C levels may result from HIV infection and/or thrombotic activity, a mediator of endothelial injury and thrombogenesis, or both.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with older reports. 17 , 37 This finding is reinforced by the progressive increase in CD4 + T-cell count as years of treatment increase. The hallmark of HIV infection and subsequently AIDS pathogenesis is a progressive depletion of CD4 + T-cell populations in close association with progressive impairment of cellular immunity and increasing susceptibility to opportunistic infections.…”
Section: Discussionmentioning
confidence: 97%
“…This observation is in agreement with previous reports. 16 , 17 This finding may be attributed to high demand in zinc because HIV nucleocapsid and integrase proteins that are essential for assembly of infectious virions contain zinc fingers that require zinc for normal structure and functioning. 18 , 19 , 20 Zinc deficiency is associated with impaired immune function 21 , 22 and an increased susceptibility to infection.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in consonance with previous findings. Depletion of CD4 + T-cell in HIV infection has been well documented [37, 44, 45]. The central event in HIV infection is destruction of CD4 + T-cells leading to a compromised immune system [46].…”
Section: Discussionmentioning
confidence: 99%